595. Changes in Ryan White Clinic Referral Patterns Among HIV-Infected Patients Following Implementation of the Affordable Care Act. (26th November 2018) - Wade, Cameron; Yang, Justin; Collins, Jana; Sanderson, Wayne; Crawford, Timothy; Thornton, Alice
Abstract: Background: The Affordable Care Act (ACA) enacted on March 23, 2010 may have subsequently affected referral patterns for persons living with HIV (PLWH). The ACA permits states to provide Medicaid for individuals at or below 138% of the federal poverty line with federal funding for 3 years after enactment. Following the Kentucky Medicaid expansion in September 2013, the uninsured rate fell from 14.3% ( 616, 000) in 2013 to 6% ( 261, 000) in 2015 (USDC, 2016). As of June 2016 the total number of diagnosed PLWH in Kentucky was 9, 928 (CHFS, 2016). This study evaluated the impact of the ACA on referrals to care for PLWH. The University of Kentucky Bluegrass Care Clinic (UK BCC) is a federally funded Ryan White HIV/AIDS clinic that serves 63 counties in central and eastern Kentucky. Methods: This study examined 1, 022 newly enrolled patients between March 24, 2010 and June 8, 2017 to observe changes in referral patterns at the UK BCC. Referral type was categorized into one of nine groups (referral by self, outpatient clinic, hospital, OB/GYN, community organization, UK BCC, transfer, health department, and unknown). Unknown observations were removed from the data analysis. Results: Of the 1, 022 intake records, 127 had an unknown referral source (12.4%). Between the period 2010–2013 (Pre-ACA) there was an 18% decrease in referrals from Health Departments between pre- and post-ACA (29.8% vs. 12.0%). In addition, there was a 13.0% increase in transfer care to the UK BCC (16.1% vs. 29.3%). There was an overall significant difference in referral care patterns between the two time periods ( P < 0.0001) when considering all referral groups. Conclusion: The decrease in referral of patient from Health Departments may indicate that PLWH have more access to screening and referrals to clinic care through primary care providers with Medicaid expansion. Further, the increase in patients who transfer from pre-existing care to the Ryan White clinic suggest that the expansion of PLWH using Medicare and Medicaid may have resulted in loss of eligibility from other HIV care providers. These results have implications to engage more PLWH into care, particularly in states that have increased access to primary care through healthcare expansions. Disclosures: All authors: No reported disclosures.